Green Synthesis of Polyvinylidene Fluoride using Xanthan Gum Biopolymer and Dimethyl Sulfoxide Green Solvent : (Journal of Applied Membrane Science & Technology, 2023)
The usage of conventional solvent during the membrane fabrication could cause undesirable negative impact to the environment. Associated with this, greener alternative to membrane synthesis has grab the attention of researchers globally. Therefore, this study explored on the green synthesis of polyvinylidene fluoride (PVDF) membrane by adopting the natural ingredient Xanthan Gum (XG) biopolymer together with green solvent dimethyl sulfoxide (DMSO) to form a new generation PVDF membrane. The membrane was prepared by phase inversion method with different XG concentration ranging from 0 wt% to 1.5 wt% while maintaining the constant PVDF and DMSO concentration. Several membrane performance tests were done which included water flux test, Congo red (CR) rejection, and flux recovery ratio (FRR). In this study, the incorporation of XG in membrane shown enhancement in membrane hydrophilicity with a noticeably reduction of wettability from 48.67o to 42.15o. The results shown that membrane embedded with 0.5 wt% XG appeared as the optimum XG concentration. As for the membrane performance, it achieved the pure water flux and FRR of 182.87 L/m2.h and 91.25%, respectively. According to the overall performance evaluation, the incorporation of XG promoted the performance of membrane.
Keywords: Xanthan gum, dimethyl sulfoxide, polyvinylidene fluoride, green synthesis, green solvent